Стан та шляхи розвитку національної системи геодезичного відліку - Карпінський, Ю.; Висотенко, Р.; Karpinskyi, Y.; Vysotenko, R. (Видавництво Львівської політехніки, 2024)
Мета дослідження – оцінити стан, виявити тенденції та напрями розвитку національної системи гео- дезичного відліку. Методика. Для опрацювання інформації щодо пошуку нових підходів до розвитку національної системи геодезичного відліку використано методи системного аналізу. Результати. В дослідженні наведено основні характеристики Державної геодезичної референцної системи координат УСК-2000. Оскільки від часу встановлення параметрів зв’язку Державної геодезичної референцної системи координат УСК-2000 із загаль- ноземною системою координат ITRS/ITRF2000 пройшло майже 20 років, зважаючи на наявність абсолютних та відносних деформацій та зміщень земної поверхні Vx, Vy, Vz, внаслідок тектонічних рухів земної кори як глобального, так і локального генезису, необхідно розвивати національну систему геодезичного відліку. Запро- поновано три варіанти її розвитку, які передбачають узгодження системи із новітніми реалізаціями Міжнародної земної референцної системи відліку, перехід від використання референтц-еліпсоїда Красовського до загально- земного еліпсоїда GRS-80 і перехід від використання проєкції Гаусса – Крюгера до картографічної проєкції Меркатора (UTM). Наукова новизна. Запропоновано три варіанти подальшого розвитку національної системи геодезичного відліку, які відповідають сучасному інформаційно-технологічному рівню формування референцних систем координат, Практичне значення роботи. Запропоновані напрями удосконалення національної системи геодезичного відліку сприятимуть розвитку національної інфраструктури геопросторових даних та об’єктивному процесу інтегрування у глобальну та європейську інфраструктури геопросторових даних.

20 years ago, the Resolution of the Cabinet of Ministers of Ukraine No. 1259 “Some issues of the application of the geodetic coordinates reference system” (the Resolution) was adopted, which at the legislative level opened the way for a new stage in the development of topographic and geodetic activities in Ukraine. The purpose of the study is to assess the state, identify trends and ways of development of the national reference system. The development of the national reference system and the State Geodetic Network is particularly relevant in the context of the development of the national spatial data infrastructure (NSDI. Three ways of further development of the national geodetic reference system are proposed. The first approach involves specifying the connection parameters of the USK-2000 state geodetic reference coordinate system to the new implementation of the ITRS / ITRF2020 system in the 2025.0 era, preserving the Krasovsky reference ellipsoid and the Gauss-Kruger map projection. The second approach also involves specifying the parameters of the connection of the state geodetic reference coordinate system USK-2000 to the new implementation of the ITRS / ITRF2020 system at the epoch 2025.0, but uses the global ellipsoid GRS-80 and the Mercator cartographic projection (UTM). The third approach involves switching to the European terrestrial coordinate system ETRS89, the global ellipsoid GRS- 80 and the Mercator cartographic projection (UTM). The determination and justification of the optimal way of development of the national geodetic reference system should be based on a comprehensive comparative analysis of possible options, taking into account the current state of development of the national infrastructure of geospatial data and the objective process of integration into the global and European infrastructure of geospatial data. Justification of the choice of one of the options for the development of the national geodetic reference system involves the involvement of the professional geodetic community in the discussion and solution of this problem.
State and ways of development of the national geodetic reference system
Keywords: Державна геодезична референцна система координат УСК-2000; Державна геодезична мере- жа України; міжнародна земна референцна система (ITRS); система координат СК-42; система координат СК-63; референц-еліпсоїд Красовського; загальноземний еліпсоїд (GRS-80); картографічна проєкція Гаусса – Крюгера; картографічна проєкція Меркатора (UTM); State geodetic coordinate reference coordinate system UCS-2000; State geodetic network of Ukraine; Krasovsky reference ellipsoid; global ellipsoid (GRS-80); Gauss – Kruger map projection; Mercator map projection (UTM). national spatial data infrastructure coordinate system; 519; 23; 528; 93